Lifetime of the phonons in the PLT ceramic (2014)
ABSTRACT: The lifetimes at higher temperatures on lanthanum-modified lead titanate (PLT) are mainly due to the anharmonic decay of optical phonons into low-energy phonons. The temperature-independent contributions from inherent crystal defects and from boundary scattering become comparable to the phonon scattering contribution at lower temperatures. The thermal interaction is large at higher temperatures which decreases the phonon mean free path, and so the decay lifetime decreases as the temperature of the system is increased. This leads to the increased line width at higher temperatures. We made an estimate of the lifetimes for different concentrations and temperatures in PLT.